Analiza pogojev zgorevanja v sekundarni komori pilotne sežigalnice na podlagi računske dinamike tekočin - Kokalj, Filip (Strojniški vestnik, 2005)
A numerical analysis of the combustion in the secondary chamber (thermoreactor) of a two-stage pilot-scale incinerator using computational fluid dynamics (CFD) is presented. The focus of the research was on those physical conditions that ensure complete combustion, i.e., temperature, residence time and turbulent mixing. Various versions of the CFD program package CFX were used; they offer different combustion models for specific types and forms of combustion processes. The selection of an appropriate combustion model was based on a comparison of the numerical results and experimental values of some combustion macro parameters in a thermoreactor. Combustion models based on a one-step bimolecular chemical reaction and modelsbased on multi-step reactions were usedč this enabled a more detailed prediction of the combustion conditions in the secondary chamber of a pilot-scale incinerator. The products of incomplete combustion that are very important for the designing and optimization of combustion devices can be predicted by applying multi-step reaction models. An ultimate analysis of the complete combustion conditions was made based on a selected combustion model by considering those different operating conditions, causing variations in thequantity, composition and heating values of the gases coming from the primary chamber. The important conclusions are that the secondary and tertiaryair intakes and the relationship between them have the greatest influence on the combustion quality in the thermoreactor.
Keywords: zgorevanje; analize numerične; modeli zgorevanja; računska dinamika tekočin; sežigalnice odpadkov; numerična analiza